2017
DOI: 10.1002/micr.30182
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular replantation of head and neck amputated parts: A systematic review

Abstract: Urgent replantation of head and neck amputated parts allow patients to recover in a timely manner and to decrease the need for secondary reconstructive procedures. The significant rate of success is a strong argument in favor of promoting access to care for replantation of craniofacial parts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…In particular, microsurgery is found to be effective for repairing avulsion wounds. [7][8][9][10][11]. For scalp replantation, early microsurgery is recommended.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, microsurgery is found to be effective for repairing avulsion wounds. [7][8][9][10][11]. For scalp replantation, early microsurgery is recommended.…”
Section: Discussionmentioning
confidence: 99%
“…Pit bull terriers are the most common identified breed in dog bites requiring surgical repair, and are also more likely to cause more severe injuries than other dog breeds (Garvey, Twitchell, Ragar, Egan, & Jamshidi, ; Golinko et al, ; Kaye et al, ; O'Brien et al, ). There have been many published reports of tissue replantation in various head and neck sites and a recent systematic review identified 208 such cases (Efanov et al, ). However, only 1 case involved the mid‐face and while the size of the replantation was large, both artery and vein were anastomosed (Cooney, Flether, & Bonawitz, ).…”
Section: Discussionmentioning
confidence: 99%
“…In the specific case of lip amputation, microsurgical replantation has the potential for superior aesthetic outcomes as well as restoration of sensory and motor function. Since James reported successful microsurgical replantation of the lip in 1976, there have only been 21 cases reported, four of which were due to human bites [1][2][3][4][5][6]. Due to the paucity of reports on this, complications are likely to be underreported.…”
Section: Introductionmentioning
confidence: 99%